Leadership Communication - Čuček, Mateja (Interdisciplinary and Applied Konwledge for Green and Digital Logistics Processes, 2026)
Communication between employees, with business partners, customers and the external public is crucial for the effective flow of information and successful collaboration within and outside an organisation. How we communicate with the external environment of the organisation is primarily a reflection of what is happening within the organisation, and leadership is key to good communication and collaboration. It is leaders who help to minimise the challenges an organisation faces by example and adopting the right approach. In doing so, it is crucial that they know themselves, how they react in various situations, the leadership style they have and that they know their employees. There are several ways to identify and align employee preferences and expectations, one of which is by conducting regular annual interviews. When an organisation has employees from different generations, it is essential that managers and all employees are also aware of the values and behaviours of each generation to gain a competitive advantage.